2019
DOI: 10.1111/cen.13990
|View full text |Cite
|
Sign up to set email alerts
|

Risk of incident circulatory disease in patients treated for differentiated thyroid carcinoma with no history of cardiovascular disease

Abstract: Context The incidence of differentiated thyroid cancer (DTC) is increasing, yet the prognosis is favourable and long‐term survival is expected. Exogenous TSH suppression has been used for many years to prevent DTC recurrence and may be associated with increased risks of circulatory diseases. Design Risks of circulatory disease in patients treated for DTC were compared to randomly matched patients without DTC (controls) up to a 1:5 ratio using age, sex, body mass index (BMI) and smoking as the matching paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
(65 reference statements)
3
23
0
Order By: Relevance
“…A recent study conducted by Toulis et al, on the other hand, proved a higher mortality rate and an higher rate of cerebrovascular events even in those subjects. 15 This study, even without any data about the degree of TSH suppression, seems consistent with the correlation that we observed between TSH suppression class and the incidence of arrhythmic events, even more significant if restricted to those subjects with no previous events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent study conducted by Toulis et al, on the other hand, proved a higher mortality rate and an higher rate of cerebrovascular events even in those subjects. 15 This study, even without any data about the degree of TSH suppression, seems consistent with the correlation that we observed between TSH suppression class and the incidence of arrhythmic events, even more significant if restricted to those subjects with no previous events.…”
Section: Discussionsupporting
confidence: 91%
“…Patients in follow up after DTC show an increased risk of cardiovascular events compared to the population with same demographic characteristics with no history of such disease. 6,[15][16][17] In the extensive analysis performed by Pajamaki et al in 2017, a significant prevalence of cardiovascular disease was proven in cancer patients, both for the events in toto and for arrhythmic events. The different incidence between cases and controls was much more evident in the younger subgroups of population (<40, 40-60 yrs), that is those in which the "basal" cardiovascular risk was lower.…”
Section: Discussionmentioning
confidence: 99%
“…TCA is considered an independent predictor for AF along with well-known AF risk factors [140,154,155]. Notably, the increased risk of AF in patients treated for DTCA but without pre-existing cardiovascular disease may warrant periodic screening for this arrhythmia [156]. This is in line with a recent study indicating that patients with DTCA along with TSH suppression below 0.1 mIU/L have a higher risk of AF [151].…”
Section: Thyroid Carcinoma Suppressive Therapy and Risk For Cardiac Asupporting
confidence: 56%
“…Four studies reported that the risk of incident AF was significantly higher in DTC patients compared to cancer-free controls, adjusted for established risk factors, such as age, hypertension, diabetes and coronary artery disease ( Klein Hesselink et al 2015 , Pajamäki et al 2018 , Suh et al 2019 , Toulis et al 2019 ), whereas another study reported a higher AF prevalence when compared to the general population ( Abonowara et al 2012 ). The sixth study included a cohort of DTC patients with low- and intermediate-risk for recurrence, examining the benefits of TSH suppression and potential skeletal and cardiovascular adverse events ( Wang et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%